ANALYSIS OF ENGLISH SENTENCE STRUCTURES IN THE SPEECH OF STUDENTS MAJORING IN ENGLISH FOR INTERNATIONALCOMMUNICATION AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY TAWAN-OK - Dandee, Warinthon; Abu Rmelah, Pawarisa (International Online Journal of Education and Teaching, 2024)
This research aims to investigate the utilization of English sentence structures in spoken language, the occurrence of errors in employing English sentence structures in spoken language, and the level of satisfaction with teaching through the B-SLIM Model. The study involved a sample of 35 first-year students enrolled in the English for International Communication program at Rajamangala University of Technology Tawan-ok. The participants were chosen through a specific sampling procedure. Data collection encompassed the utilization of 7 B-SLIM Model lesson plans. The research design included a pre-test and post-test on English speaking abilities. Additionally, a satisfaction questionnaire gauging students’ contentment with B-SLIM Model learning activities was administered, along with a focus group session that delved into the reasons behind speaking errors. The collected data underwent analysis to determine the mean, standard deviation, and percentage. The findings revealed that students employed singular sentences in the form of declarative statements with using the active voice. Following the integration of B-SLIM Model lesson plans into the curriculum, students demonstrated an enhanced ability to construct compound sentences, complex sentences, and compound-complex sentences. Regarding the occurrence of errors in employing English sentence structures within spoken language, the errors were categorized based on word type and word order.